Quality and Safety Assessment of Honey Imported from Ukraine to Poland: Physicochemical and Residue Analysis - Jaśkiewicz, Katarzyna; Szczęsna, Teresa (Journal of Apicultural Science, 2025)
The aim of the study was to determine whether honey imported to Poland from Ukraine meets the quality standards and whether it is free of residues of plant protection products in accordance with the maximum permissible residue levels (MRLs). Due to the relatively small number of samples analysed (n=20), the results obtained in our study may not be fully representative for Ukrainian honey imported to Poland. Nevertheless, the pollen spectrum of Ukrainian honeys imported to Poland is characteristic for the climatic zone of Eastern and South-Eastern Europe. The majority of honey imported from Ukraine to Poland meet the quality requirements stated in EU regulations. Residues of plant protection products in Ukrainian honey imported to Poland do not exceed the MRLs. Adherence to quality standards and regular monitoring of honey parameters imported from Ukraine to Poland are key to ensuring the high quality and safety of honey on the Polish market.